1984
DOI: 10.1029/jb089ib02p01089
|View full text |Cite
|
Sign up to set email alerts
|

A detailed view of the South Pacific geoid from satellite altimetry

Abstract: Images of sea surface undulations in the South Pacific have been constructed from GEOS 3 and SEASAT altimeter data. Height discrepancies at crossover points, associated with long‐wavelength radial orbit error, were suppressed by taking along‐track derivatives of the ascending and descending profiles. These geoid slopes were then rotated and scaled to produce the north and east components of the deflection of the vertical. Finally, the results are displayed by using the hill shading technique, where gray‐tone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 47 publications
(68 reference statements)
1
56
0
Order By: Relevance
“…From a knowledge of the regional depth (about 5600 m) and of the history of adjacent portions of the Pacific Ocean, it was inferred only that the lithosphere at Site 595 had been produced at a fast-spreading ridge at high southern latitude sometime during the Mesozoic. The geoid calculated from satellite altimetry suggested that there were no substantial bathymetric or tectonic features in the immediate area (Sandwell, 1984;Dixon and Parke, 1983).…”
Section: Regional Settingmentioning
confidence: 99%
“…From a knowledge of the regional depth (about 5600 m) and of the history of adjacent portions of the Pacific Ocean, it was inferred only that the lithosphere at Site 595 had been produced at a fast-spreading ridge at high southern latitude sometime during the Mesozoic. The geoid calculated from satellite altimetry suggested that there were no substantial bathymetric or tectonic features in the immediate area (Sandwell, 1984;Dixon and Parke, 1983).…”
Section: Regional Settingmentioning
confidence: 99%
“…Satellite altimetric data have facilitated the detection of long volcanic chains in oceanic basins [Sandwell, 1984;Sandwell and Smith, 1995;Haxby, 1987;Mayia and Diament, 1991]. Recent work on the relationship between axial and offaxial volcanism has suggested that most volcanic structures found on ridge flanks could be related to magmatic processes taking place underneath accreting plate boundary regions [Batiza, 1989;Hekinian et Mammerickx, [1992].…”
Section: Introductionmentioning
confidence: 99%
“…Single-satellite and dual-satellite crossovers were performed, and at the crossover positions, north(ξ ) and east(η ) components of deflections of the vertical were determined using Sandwell's computational philosophy, and expressed as [11] :…”
Section: Computing Deflections At Crossover Locationsmentioning
confidence: 99%